Effect of Steam Pressure and Conditioning Temperature During the Pelleting Process on Phytase Stability - C. N. Truelock; N. E. Ward; J. W. Wilson; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2019)
This experiment was designed to evaluate the effects of steam pressure and conditioning temperature on the stability of microbial phytase. Treatments were arranged as a 2 × 3 factorial of steam pressure (24 and 44 psi) and conditioning temperature (170, 180, and 190°F). Phytase was added to a corn-soybean meal-based diet and mash samples were collected for phytase analysis. The diet was pelleted via steam conditioning (10 × 55 in Wenger twin staff pre-conditioner, Model 150) and using a pellet mill (CPM Model 1012-2) with a 3/16 × 1 1/4 in pellet die (L:D 6.7). Conditioner retention time was set at 30 sec and production rate was set at 33 lb/min, approximately 100% of the rated throughput for the pellet mill. All treatments were replicated on 3 separate days. For each treatment, pellet and conditioned mash samples were composited such that 2 samples of each were analyzed for phytase activity and pellet durability index (PDI). Moisture analysis was conducted on initial mash, conditioned mash, hot pellet, and cooled pellet samples. Conditioning temperature, hot pellet temperature (HPT), and production rate were recorded throughout each processing run. Data were analyzed using the GLIMMIX procedure in SAS 9.4, with pelleting run as the experimental unit and day as the blocking factor. There was no evidence (P>0.17) for a steam pressure × conditioning temperature interaction for HPT, phytase stability, moisture, or PDI. Increasing conditioning temperature from 170 to 190°F increased (linear,P<0.01) HPT. There was no evidence for difference (P= 0.80) in HPT between steam pressures. Phytase stability of conditioned mash decreased (linear,P<0.01) with increasing conditioning temperature. In cooled pellets, phytase stability decreased (linear,P<0.01) with increasing conditioning temperature. Cooled pellets tended (P= 0.08) to have greater phytase stability when steam pressure was set at 44 psi compared to 24 psi. Moisture of conditioned mash and pellets increased (linear,P≤ 0.05) with increasing conditioning temperature, and PDI tended (linear,P= 0.06) to increase with increasing conditioning temperature. There was no evidence (P>0.35) that steam pressure affected feed moisture or PDI. Results of this experiment show that phytase stability in conditioned mash and pellets decreases linearly when the conditioning temperature rises above 170°F and HPT above 179°F. As expected, HPT increased and feed moisture tended to increase with increasing conditioning temperature. Increasing steam pressure from 24 to 44 psi resulted in tendencies for greater phytase stability in pellets and had no effect on HPT or feed moisture.
Keywords: conditioning temperature; pelleting; phytase stability; steam pressure